(untitled) (Per Musi, 2022)
The actuality of a symbiosis between art and media, our object of study, presents itself in close relationship with the human aspect of ancient Greek reflection on art. In order to investigate the role of this relationship for contemporary understanding on possible social “places” of art, we relate the term μουσική τέχνη (mousikḗ tékhnē) to telematics, as described by Vilém Flusser, which means the consideration of otherness and altruism in aesthetic fruition. Thus, our methodology places music in front of the current post-humanist reflection, that discusses the social, political and ecological scope of a collective altruism, which we contextualize here in the symbolic aspect of music and in its fruition. Our conclusions include the discussion about the resort to a Greek heritage, the echoes of utilitarianism and the understanding of art as a collective and altruistic form of human interrelationship.